MONITORING MANGROVE COVER DYNAMICS FOLLOWING SHRIMP POND EXPANSION USING NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) ANALYSIS IN BULAKSETRA, PANGANDARAN - Hakim, Muhammad Romdonul; Firdaus, Anas Noor; Baswantara, Arif; Kelana, Perdana Putra (Politeknik Kelautan dan Perikanan Dumai, 2025)
The mangrove ecosystem along the coast of Bulaksetra, Pangandaran, West Java, plays a crucial role in mitigating potential tsunami disasters. However, over the last five years, the Bulaksetra mangrove ecosystem area has seen intensive operation of local shrimp ponds, which has negatively impacted the growth and health of the surrounding mangrove stands. This study aims to monitor the changes in mangrove cover from 2020 to 2024 within the Bulaksetra mangrove ecosystem using Sentinel-2 satellite imagery. The methodology employed to determine the extent and condition of mangrove cover involves the analysis of the Normalized Difference Vegetation Index (NDVI) processed using the Google Earth Engine (GEE) platform. The results indicate significant habitat degradation within the Bulaksetra mangrove ecosystem, evidenced by a 96.94% loss of the Dense canopy class by 2024. This shift in density class is characterized by a transition from the Dense class to the Sparse (54.37%) and Moderate (42.58%) classes, accompanied by a 5.18% decrease in the total mangrove area. Conversely, the area occupied by shrimp ponds has continuously expanded, with a growth rate reaching 1.31 hectares per year. The expansion of shrimp ponds demonstrates a negative correlation with mangrove cover in the Bulaksetra mangrove area during the 2020 – 2024 period.